PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK BERBASIS AUDIO PADA MATERI BANGUN DATAR SEGIEMPAT DI SMP - Baiduri Baiduri; Marhan Taufik; Lufita Elfiani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
This study aimed to develop the learning media and investigated the effectiveness of audio-based Pop-Up Book media on the two-dimensional rectangular shape. This media was tested twice in a small group of 6 students and in a large group of 25 students. Respondents were the 7th grade students. The result of expert validation showed the average percentage of 88,16 % and was considered valid, thus the learning media was allowed to be used and tested. The analysis of effectiveness in small and large groups in a row revealed that students’ respond was very good, with the percentage of 88.1% and 88.87%. In addition, the activities of students in the class were very good, showed by the percentage of 92% and 86.8%. Finally, the classical completeness of the learning outcomes obtained the percentage of 100% from 6 students and 92% from 23 students who completed the test. Therefore, it can be concluded that the application of audio-based Pop-Up Book on the two-dimensional rectangular shape was effective for Junior High School students.